ANALISIS NILAI-NILAI ADAB PEREMPUAN BERBASIS AYAT-AYAT NISAIYYAH DALAM AL QUR’AN - Suhebah, Enong; Susilawati, Nofa Nur Rahmah (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2022)
Women have an important role in all aspects of family life and public life. The rolr of women is very meaningful in realizing, the ideals of developing religions, national and state life. Therefore, women’s empowerment is hoped that it will be more focused on correct and quality womenns education, so women are able to carry out their duties both in the domestic sector and the public sector. Advances in science and technology , it is verry possible for a shift in women’s gait from ideal concept to reality. Where women are required to undergo a dual role, namely the public sector and the domestic sector. Of course in this case it is not a problem, as long a women can be wise in dealing whit it. But in reality, sometimes women are more dominated by their demands on public roles than women on a domestic role. These problems encourage the need for an in depth study of how the values of women’s etiquette education are based on the Qur’an, so relefant to the advancement of science and tecknology in this third millennium. This resech is qualitative in the form of a study of nisaiyyah verses the Qur’an. The values of adab education based on nisaiyyah verses in the Qur’an are expected to be a rabbis who are able to raise the dignity of religion and this nation. Research results A woman based on the Nisaiyah verse has the competence to carry out her mandate as a woman both in the domestic and public spheres.